2018
DOI: 10.3389/fonc.2018.00456
|View full text |Cite
|
Sign up to set email alerts
|

The Identification of Immunological Biomarkers in Kidney Cancers

Abstract: The recent approval of several agents have revolutionized the scenario of therapeutic management of metastatic renal cell carcinoma (RCC) allowing us to reach important clinical end points with extended patients' survival. Actually, every new drug approved has represented an important step forward to the improvement of patient's survival. On the other hand, we now understand that RCC includes a large group of tumor entities, each of them with different genetic and mutational alterations, but also showing diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 125 publications
0
31
1
Order By: Relevance
“…Additionally, for patients who initially respond, many will progress while on treatment as tumor cells develop resistance 49 , 51 . Ongoing efforts seek to identify and confirm clinically relevant predictive biomarkers in ccRCC to aid clinicians in immunotherapy selection 52 , 53 . As such, model systems capable of recapitulating the TME are crucial to enhance our understanding of drug interactions.…”
Section: Biomarker Development and Treatment In Advanced Ccrccmentioning
confidence: 99%
“…Additionally, for patients who initially respond, many will progress while on treatment as tumor cells develop resistance 49 , 51 . Ongoing efforts seek to identify and confirm clinically relevant predictive biomarkers in ccRCC to aid clinicians in immunotherapy selection 52 , 53 . As such, model systems capable of recapitulating the TME are crucial to enhance our understanding of drug interactions.…”
Section: Biomarker Development and Treatment In Advanced Ccrccmentioning
confidence: 99%
“…The prognosis of advanced RCC is poor in part because RCC is often resistant to traditional therapies such as radiation therapy and chemotherapy. Epidermal growth factor receptor‐tyrosine kinase inhibitors and immunocheckpoint inhibitors targeting PD‐1 or its ligand PD‐L1 showed promising therapeutic efficacy in advanced RCC . Recent reports showed that the expression of EGFR and PD‐L1 is a poor prognostic factor in RCC .…”
Section: Introductionmentioning
confidence: 99%
“…Epidermal growth factor receptor-tyrosine kinase inhibitors and immunocheckpoint inhibitors targeting PD-1 or its ligand PD-L1 showed promising therapeutic efficacy in advanced RCC. [3][4][5][6][7] Recent reports showed that the expression of EGFR and PD-L1 is a poor prognostic factor in RCC. 6-8 Prognostic biomarkers are important in the guidance of therapeutic options and…”
mentioning
confidence: 99%
“…While immune checkpoint inhibitors have been successful in advanced ccRCC patients, not all patients respond to these inhibitors. Thus, there is an important clinical need to identify biomarkers for these promising therapies . Related to this, while higher PD‐1 and PD‐L1 expressions in primary tumors have shown to predict poor survival, their role in selecting patients for immune checkpoint inhibitors remains unclear .…”
Section: Introductionmentioning
confidence: 99%